Ist es der Sindtfluss? - Kulturelle Strategien & Reflexionen zur Prävention und Bewältigung von Naturgefahren - Lackner, Reinhard (alpine space - man and environment, 2008)
In a mountainous area like Austria alpine hazards are a safety risk: floodings, landslides, avalanches, and rockfalls endanger man, human settlements, living space, and economic area. Adaptation to climate change requires particular precautions for human living spaces. Traditional measures and the traditional perception of natural disasters give a clue to the management of future scenarios. This intangible heritage fosters sustainable developments by education.